Love: A phenomenological inquiry into the self-other relation in Sartre and Beauvoir - De La Cruz, Noelle Leslie G. (Animo Repository, 2007)
The author explores the views of two famous philosophers and one-time lovers about the self-other relation, particularly in the context of romantic love. In Being and nothingness (1956), Jean-Paul Sartre famously wrote that any mode of relation between two subjectivities is doomed to fail. One of these modes is love, which is the desire to possess another freedom without altering its fundamental characteristic as a freedom. In contrast to Sartre, meanwhile, Simone de Beauvoir hints at the possibility of non-possessive reciprocal relations in her philosophical novel, She came to stay (1943). In light of such considerations as the relationship between love and the construction of self, and that between love and freedom, Dela Cruz evaluates the respective merits of the two thinkers' views. She concludes the paper with a brief analysis of the lyrics of a contemporary song performed by Seal, entitled "Love's Divine." The song has an existential theme as it links love with the naming of another subjectivity: "Give me love, love is what I need to help me know my name.".